Teaching Methods and the Implementation of Multicultural Education in Cameroon’s Primary Schools, Perceptions of Some Educational Stakeholders in Fako Division of the South West Region of Cameroon - Mbah, Emmanuel TEKE (Journal of Innovation in Education and Social Research, 2024)
In this paper, the author discusses teaching methods in the implementation of multicultural education from the viewpoint of educational stakeholders in Cameroon within a qualitative, interpretivist paradigm. He situates in context the multicultural structure of Cameroon schools. He argues that cultural diversity is an addition teachers need to consider in content delivery, such that all students have access to equitable educational experiences that benefit from their multicultural backgrounds. Through qualitative research supported by some quantitative data, the focus is made on the perception of educational stakeholders in Fako Division of the South West Region of Cameroon on the methods of teaching multicultural classrooms. Parents, primary school teachers, head teachers and inspectors of basic education perceptions were collected using a questionnaire, interview guide, and focus group discussion. The interview guide and the focused group discussions were organized into different sections which responded to the different research questions and were analyzed as such. The findings revealed that; there is a total agreement rate of 81% on the proposed teaching material for multicultural education. This implied that the stakeholders found the proposed teaching materials for teaching multicultural education very useful. Direct instruction, dramatization, early initiation to language and allocation of teaching hours for multicultural education were found to be important in the teaching of multicultural education. The author concludes that policy modification and teacher development must take into account the complex multicultural realities in schools and classrooms to provide equitable education for all learners.